Direct laser patterning of a 2D WSe2 logic circuit - Zhu, Chao (2021)
Carrier doping is the basis of the modern semiconductor industry. Great efforts are put into the control of carrier doping for 2D semiconductors, especially the layered transition metal dichalcogenides. Here, the direct laser patterning of WSe2 devices via light‐induced hole doping is systematically studied. By changing the laser power, scan speed, and the number of irradiation times, different levels of hole doping can be achieved in the pristine electron‐transport‐dominated WSe2, without obvious sample thinning. Scanning transmission electron microscopy characterization reveals that the oxidation of the laser‐radiated WSe2 is the origin of the carrier doping. Photocurrent mapping shows that after the same amount of laser irradiation, with increasing thickness, the laser patterned PN junction changes from the pure lateral to the vertical‐lateral hybrid structure, accompanied by the decrease in the open circuit voltage. The vertical‐lateral hybrid PN junction can be tuned to a pure lateral one by further irradiation, showing possibilities to construct complex junction profiles. Moreover, a NOR gate circuit is demonstrated by direct patterning of p‐doped channels using laser irradiation without introducing passive layers and metal electrodes with different work functions. This method simplifies device fabrication procedures and shows a promising future in large scale logic circuit applications.